Topical estrogen prescribing patterns for urogenital atrophy among women with breast cancer: results of a national provider survey. Issue 7 (July 2019) - Richter, Lee A.; Han, Jim; Bradley, Sarah; Lynce, Filipa C.; Willey, Shawna C.; Tefera, Eshetu; Pollack, Craig E.
Abstract: Objective: The aim of the study was to evaluate knowledge, attitudes, and practice patterns of physicians prescribing topical estrogen for women with urogenital atrophy and a history of breast cancer. Methods: A cross-sectional survey of breast surgeons, urogynecologists, and gynecologists was distributed via their professional societies: the American Society of Breast Surgeons (ASBrS), the American Urogynecologic Society (AUGS), and the Society of Gynecologic Surgeons (SGS). Providers reported level of comfort prescribing vaginal estrogen for urogenital symptoms for women with different categories of breast cancer and current treatment: estrogen receptor (ER) negative, ER positive no longer on endocrine therapy, and ER positive currently on adjuvant endocrine therapy. General knowledge questions assessed agreement on a 5-point Likert scale to statements about vaginal estrogen safety and pharmacology. Results: A total of 820 physicians completed the survey: 437 responses from the ASBrS (response rate, 26.7%), 196 from AUGS (15%), and 187 from SGS (44.5%). The majority of physicians (84%), regardless of specialty, felt comfortable prescribing vaginal estrogen to women with a history of ER-negative cancer: 65.7% felt comfortable prescribing for women with ER-positive breast cancer no longer on endocrine therapy; 51.3% for women on an aromatase inhibitor; and 31.4% for women on tamoxifen. Urogynecologists were significantly more comfortable than breast surgeons prescribing vaginal estrogen for the lowest risk patients, whereas breast surgeons had the highest level of comfort for women currently on endocrine therapy. Conclusions: This study highlights heterogeneity in practice patterns both within and across specialties. The clinical variation seen in this study suggests providers may benefit from increased knowledge regarding vaginal estrogen.